Management of Microsurgical Patients using Intraoperative Unfractionated Heparin and Thromboelastography - Zavlin, Dmitry; Chegireddy, Vishwanath; Jubbal, Kevin T.; Agrawal, Nikhil A.; Spiegel, Aldona J. (Journal of Reconstructive Microsurgery, 2019)
Background Maintaining optimal coagulation is vital for successful microvascular tissue transfer. The viscoelastic thromboelastography (TEG) is a modern and dynamic method to assess a patient's coagulation status. The aim of this study was to evaluate its diagnostic capabilities of identifying microvascular complications.Methods A retrospective chart review was conducted for the most recent 100 cases of abdominal free flap breast reconstruction of a single surgeon. Patient demographics, medical history, clinical, and operative details were documented. Thrombocyte counts, prothrombin time (PT), activated partial thromboplastin time (aPTT), and various TEG parameters were gathered for preoperative, intraoperative, and two postoperative time points.Results A total of hundred patients were identified, who underwent 172 abdominal-based free flaps for breast reconstruction. TEG was more dynamic compared with PT or aPTT and demonstrated borderline hypocoagulate values intraoperatively upon unfractionated heparin administration and hypercoagulate values postoperatively. In contrast, PT and aPTT demonstrated a continuously hypocoagulable state. Complications included five thrombotic events and three hematomas. The thrombotic cases had much steeper increases of TEG-G between surgery and postoperative day 2 (p = 0.049), while PT and aPTT failed to identify these patients. Of those, two resulted in flap loss (1.2%) that both occurred in patients with abdominal scars from previous surgery.Conclusion The TEG is a useful adjunct for monitoring coagulation status in microsurgical breast reconstruction. When thrombosis at the anastomosis occurs, TEG correlates with a more rapid rebound from an intraoperative hypocoagulable state to a postoperative hypercoagulable state, when using the TEG. The TEG is a valuable tool for a more dynamic assessment of the patients' changing coagulation status.
Keywords: microsurgery; breast reconstruction; thrombosis; coagulation; anticoagulation; thromboelastography